PENGEMBANGAN KARAKTER DENGAN PEMBIASAAN PADA ANAK USIA 5-6 TAHUN DI TK SANTA MARIA PONTIANAK - Agustina Tania; M. Chiar; Desni Yuniarni (Universitas Tanjungpura, 2018)
AbstractSpecific problems in this study are: How does the implementation of learning using habituation in children? what efforts do teachers in developing the character of children? What constraints faced by teachers in using habituation to develop the character of the child? what are the teachers doing to overcome obstacles in using habituation to develop a child's character ?. This study was conducted on children aged 5-6 years. Techniques and data collection tools of obeservation guidelines, interview guides, field notes and documentation. Data collected by researcher in developing child character by habit, from 32 children there are 28 children come in school on time without guidance of teacher with BSB category, 4 children come in school with guidance of teacher with category of BSH, 27 children line up neatly without help of teacher with category BSB, 5 children lined up neatly with the help of teachers with the category of BSH, 28 children prayed well without the guidance of teachers with BSB category, 4 children can pray with the guidance of teachers with BSH category, 32 children tidy shoes and wash hands without the help of teachers with BSB category, 27 children completed their duties without the help of the teacher with the BSB category, 5 children completed their duties with the help of teachers with BSH category, 29 children behave and speak politely without the help of the teacher with BSB category, 3 children can behave and speak politely with the help of teacher with BSH category. Keywords: Character Development, Habituation Method.